Developing a sustainable model of a waqf-based takaful model for flood victims in Malaysia - Che Mohd Salleh, Marhanum; Razali, Siti Salwani; Kassim, Salina; Abdullah, Nurdianawati Irwani; Abdul Razak, Dzuljastri; Megat Laksana, Nan Noorhidayu; Che Embi, Nor Azizan; Mustapha Kamal, Bidayatul Akmal (2018)
The flood that occurred in late December 2014 was an unprecedented act of nature that displaced hundreds of thousands of Malaysians from their homes and causing massive damage estimated at nearly one billion ringgits. Due to the lack of unpreparedness for such an event, homes, belongings and lives were unfortunately lost in the flood-waters; the extent to which could possibly be reduced if proper pre-emptive mechanisms are well-planned ahead. This research aims to conceptualise a Takaful model based on Waqf principle as a financial preparation for the flood victims. In efforts to achieve this objective, two stages of data collection have been conducted which are survey and followed by focus group discussion (FGD). A total of 537 flood victims have involved in the survey mainly from areas affected by flood at east-coast of Malaysia (Kelantan, Pahang and Terengganu). In details, they were basically being affected mostly in the aspect of financial matters rather than health aspect. In addition, majority of them were not participated yet in the Takaful and hence they have shown their willingness to participate in the scheme in future. Meanwhile, in terms of level of awareness towards Takaful, the result indicates that they still have low level of awareness towards Takaful. Based on structural equation modelling analysis, it is found that the factors that have significantly influenced the victims to participate in the Takaful scheme are their awareness on the scheme and the financial effect. Subsequently, a qualitative data collection has been carried out via focus group discussion among the authority bodies which include government bodies, Malaysian Takaful Association, Takaful operators, and also Waqf institutions to generate idea to structure a suitable Takaful model for the flood victims. Among the three waqf-based models being considered, the third model which involves multi-sources multi-usages waqf-based Takaful model is most viable because it provides with more stable sources of funding due to diversified sources of funds. As suggested from the practitioners, there are several areas for further refinement of the model. First, it is suggested that the model to focus more on providing the takaful protection to the flood victims rather than developing the flood evacuation centre. Second, it is cumbersome to structure such a complex takaful product, thus a longer time is required in designing and implementing the product. Third, due diligence needs to be exercised to ensure the marketability and sustainability of the product, and this would further prolong the process of designing the product. Regulatory constraints pertaining to the administration of waqf-based products would also be a challenge in implementing the product. Last but not least, the product would require substantial seed capital to start off, which could be an issue due to the currently tight government financial position. Ultimately, this research aims to assist the country to reduce cost caused by the flood in the event of its future re-occurrence. The results from the survey would provide important inputs on the efforts to structure a comprehensive Waqf-based Takaful model for flood victims in Malaysia. An aspect of novelty of this research is that it applies the real objectives of Takaful as well as combines it with the Waqf principle to help one and another in times of crisis and instill brotherhood spirit in the society. More importantly, the proposed model would assist the Malaysian government to effectively channel the financial resources via a systematic way for the benefit of the flood victims, thereby reducing the financial burden incurred due to the flood disaster. On top of that, various efforts should be done by the industry to increase the level of awareness among the Malaysian on the importance of participating in the takaful plan.